2007
DOI: 10.1016/s0140-6736(07)61515-3
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 infection of the respiratory tract and beyond: a molecular pathology study

Abstract: In addition to the lungs, H5N1 influenza virus infects the trachea and disseminates to other organs including the brain. The virus could also be transmitted from mother to fetus across the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
334
6
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(371 citation statements)
references
References 37 publications
25
334
6
6
Order By: Relevance
“…Multiorgan spread and systemic virus replication are common features of pathogenic human and avian H5N1 (59,60) or avian/ equine H7N7 (60) infections of mice, but they are rare complications following inoculation with other human strains, even with the virulent 1918 H1N1 pandemic virus (61). In general terms, seasonal human influenza viruses remain confined to the respiratory tract in the mouse model, as the protease enzymes required to cleave viral HA0 are common in the lungs and trachea but not in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Multiorgan spread and systemic virus replication are common features of pathogenic human and avian H5N1 (59,60) or avian/ equine H7N7 (60) infections of mice, but they are rare complications following inoculation with other human strains, even with the virulent 1918 H1N1 pandemic virus (61). In general terms, seasonal human influenza viruses remain confined to the respiratory tract in the mouse model, as the protease enzymes required to cleave viral HA0 are common in the lungs and trachea but not in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that type II cells also express influenza virus receptors (17)(18)(19)(20). In fact, avian influenza H5N1 virus has also been detected in type II cells of humans who died during infection (31). The adaptive immune system becomes activated during infection and responds by creating virus-specific CD8 1 CTLs and antibodies that help clear virus and provide protection against subsequent infection (21).…”
Section: Discussionmentioning
confidence: 99%
“…La virémie est très inconstante au cours de la grippe saisonnière, tout comme la transmission transplacentaire au foetus (revue dans [19]). À l'inverse, plusieurs cas de passage transplacentaire du virus H5N1 ont été documentés [20], par la présence d'ADN viral dans le cytotrophoblaste [21]. Dans une série anglaise portant sur 3 975 femmes, aucun cas d'infection foetale à influenza n'a pus être mis en évidence par la recherche d'IgM dans le sang de cordon [22].…”
Section: Morbi-mortalité Affectant Le Foetus Et La Grossesseunclassified